IRRIGATED HYDROMORPHIC SOILS OF THE SOKH FUNE OF THE FERGANA VALLEY (Proceedings of International Educators Conference, 2023)
The article describes the agrochemical state of meadow alluvial and meadow saz soils irrigated by the Sokh river basin from the mountain rivers of the Fergana Valley. According to them, the content of humus in soils ranges from 0.6 to 1.2%, nitrogen - 0.03-0.11%. The content of phosphorus is 0.10-0.13%, potassium 1.70-2.10%.